Gas-phase DFT studies, quantum chemical calculation and 3D energy framework analysis of novel copper complex of sulfadimethoxine in the presence of secondary ligand 3-methyl pyridine. Issue 12 (29th September 2021) - Socha, Bhavesh N.; Pandya, Sachin B.; Chavda, Bhavin R.; Chaudhary, Kaushik P.; Padariya, Taruna J.; Alalawy, Mohammed Dawood; Dubey, Rahul P.; Patel, Urmila H.; Patel, R. H.
Abstract: Synthesis and crystal structure with extensive biological activity of the copper sulfadimethoxine complex in the presence of secondary ligand 3-methyl pyridine (title molecule) has been reported earlier. Crystal structure of the title molecule crystallizes in monoclinic space group P2 1/n . The extension of this work, stability, and reactivity of the title molecule are carried out in the DFT platform using Schrödinger software at B3LYP/LAV2P** level. The theoretically optimized structure of the title molecule in gaseous phase is well matched with the X-ray data. The chemical nature of molecule can be analyzed by employing quantum chemical calculations and HOMO-LUMO energies of the title molecule show the charge transfer occurs within the molecule. The individual atomic charge values are obtained from the Mulliken population analysis (MPA), which reveal the binding site of the title molecule. The stability of the title molecule arising from hyper-conjugative interactions and charge delocalization have been analyzed using natural bond orbital (NBO) analysis. The effect of nitrogen and oxygen atoms on weak intermolecular interactions has been systematically analyzed via energy framework analysis for title molecule. The molecular docking study has been confirmed the title molecule interacts with DNA in a groove binding site.